Nocardia farcinica brain abscess with torque teno virus co-infection: A case report - Yuting Gu; Zide Wang; Xiaohua Xia; Guang Zhao (Heliyon, 2024)
Background: Brain abscesses caused by Nocardia are rare and difficult to diagnose. Nocardia farcinica is among the most common species; however, the conventional diagnosis of N. farcinica infection consists of cerebrospinal fluid (CSF) and blood culture and Gram staining. These procedures prolong the time to diagnosis and initiating treatment. Case presentation: A 69-year-old woman with diabetes mellitus presented with headaches and dizziness persisting for 2 weeks, which was initially diagnosed as a brain abscess. Due to the unusual presentation and rapid progression of symptoms, she underwent surgical resection of the brain abscess. No pathogens were detected in blood or CSF cultures. However, metagenomic next-generation sequencing (mNGS) identified N. farcinica and Torque teno virus in pus extracted from the abscesses. The patient received appropriate antibiotic therapy and recovered fully without any residual neurological deficits. Conclusion: mNGS useful for prompt diagnosis and selection of antibiotic therapy for brain abscesses caused by Nocardia. Surgical intervention is necessary in some cases.